Realization path and connotation of the Healthy China strategy: macroscopic perspective of dietary structure and the entry of individual health consciousness - Xiaohua Zhu; Yan Zhang; Yuanyuan Zhu; Youhua Guo; Yunjin Zhang; Bin Wen (BMC, 2024)
Abstract Background Dietary rationality and health concept have certain influence on individual health level. This study aims to explore the characteristics and existing problems of Chinese residents' health behaviors from both macro and micro perspectives, and explore the feasibility and realization path of Healthy China strategy. Methods We utilized regression models to evaluate the correlation between diet and the risk of disease causes of death. By use of the linear regression analysis model, we distinguished the impact of each dimension on health literacy index at the individual level. Then, we explored the influential factors of the diet health index using the binary logit regression model. Results Increased consumption of animal-derived foods in China has contributed to the burden of non-communicable diseases. The individuals' health awareness is still weak, and the health literacy index is greatly affected by the diet, while the individual gender and age are positively correlated with the diet health index, and the individual body mass index (BMI) level is negatively correlated with the diet health index. Conclusions This study provided a comprehensive understanding of existing problems of Chinese residents' health behaviors. We have proposed a path model for the implementation of the Healthy China strategy from the perspectives of "diet health, physical health, conceptual health and environmental health," which is also a great contribution to the world.